Percepções e atitudes de moradores rurais em relação ao macaco-prego, Sapajus nigritus (Goldfuss, 1809), na área de influência de uma usina hidrelétrica no Rio Grande do Sul - Rocha, Lara Cristiani (2013)
Crop raiding by wild animals is becoming increasingly common. In recent years, the management company of the Dona Francisca Hydroelectric Power Plant has received complaints from local residents about a supposed increase in the population of capuchin monkeys, which were allegedly causing "losses" to some farming households. It is crucial to understand people´s perceptions and attitudes towards monkeys to clarify the social factors that intensify conflicts, as well as the factors which favor the coexistence between humans and capuchin monkeys in farmlands. To identify human-wildlife conflicts and their possible causes, this study investigated the perceptions and attitudes of rural community residents in Ibarama (in the Brazilian state of Rio Grande do Sul), in the vicinity of the Dona Francisca dam, with respect to capuchin monkeys. The study was carried out through semi-structured interviews with farm owners and the subsequent categorization of their answers. Thirty-one interviews were conducted between September 2010 and January 2012. Most respondents were over 40 years old and had been living in the area since childhood. Most of them stated that monkeys have always existed in that region, and only two respondents associated the "emergence" of monkeys and the building of the dam. Maize is the main crop consumed. A significant portion of the respondents claimed that monkeys cause damage to their property, but most of them could not estimate the extent of their loss. Nevertheless, most of them consider monkeys to be important to nature and believe that the coexistence of humans and monkeys is possible in those areas. Although these losses financially commit some properties, you can see a scenario favorable to the adoption of conservation and educational practices aimed at protecting the capuchin monkey and its habitat.